2008
DOI: 10.1016/j.ejvs.2007.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Effectiveness of Endovenous Laser Ablation (EVLA) in the Treatment of Great Saphenous Vein Reflux

Abstract: ED (J/cm) of laser delivery is the main determinant of successful GSV ablation following EVLA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
1
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(96 citation statements)
references
References 17 publications
8
82
1
5
Order By: Relevance
“…In this study the energy required based the size of the vein, if the vein size is less than 6 mm size 50j/cm ,6-8 mmsize 60j/ cm,8-10 mmsize,72 j/cm more than 10 mm 82 j /cm are associated with least complication [4,5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study the energy required based the size of the vein, if the vein size is less than 6 mm size 50j/cm ,6-8 mmsize 60j/ cm,8-10 mmsize,72 j/cm more than 10 mm 82 j /cm are associated with least complication [4,5].…”
Section: Resultsmentioning
confidence: 99%
“…The Energy required is directly related to the size of the vein (Table )with 810nm wave length in continuous mode achieved 90-100% occlusion of diseased veins [4,5].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…They emphasized that the higher amount is effective and safe for EVLA treatment. Theivacumar et al (20) reported that the energy amount is the main parameter that affects treatment success, and that 60/cm −1 or greater should be used for successful treatment. In contrast, Kim et al (21) reported 100% technical success using 35.16/ cm −1 in 34 patients.…”
Section: Discussionmentioning
confidence: 99%
“…26 It is possible to provoke adequate closure of the vein using 35, 60 or 80 J/cm; so a safe LEED level was used for treatment with both the bare and the radial fibers. 15,27,28 With relation to the frequency of paresthesia, it was found that tumescence played a protective role with regard to occurrence of paresthesia during the postoperative period, and the comparison with the conventional fiber at 7 days was significant (23.33% vs. 60%). The difference was not statistically significant for the comparison with the double radial fiber group, even though the latter was treated with a greater quantity of energy.…”
Section: 24mentioning
confidence: 99%